UKURAN PERUSAHAAN, PERTUMBUHAN, DAN STRUKTUR MODAL SEBAGAI DETERMINAN PROFITABILITAS PERUSAHAAN - Swaputra, Ida Bagus; Astakoni, I Made Purba; Ratini, Putu Mela; Harwathy, Tjok Istri Sri (Jurnal Riset Akuntansi (JUARA), 2018)
The purpose of this research is; (1) Analyze and explain the influence of company growth on profitability (profitability) at PT. Mustika.Ratu and Subsidiaries; (2) Analyze and explain the influence of company growth on capital structure at PT. Mustika.Ratu and Subsidiaries; (3) Analyze and explain the influence of capital structure on profitability at PT. Mustika.Ratu and Subsidiaries (4) Analyze and explain the effect of firm size on profitability at PT. Mustika.Ratu and Subsidiaries; (5) Analyze and explain the effect of firm size on capital structure at PT. Mustika.Ratu and Subsidiaries (6) Analyzing the role of capital structure in mediating the relationship of growth and firm size to profitability at PT. Mustika Ratu and Subsidiaries. Data analysis technique using Partial Least Square (PLS) approach. PLS is a model of Structural Equation Modeling (SEM) equations based on components or variants. In PLS path modeling there are two models: outler model and inner model, where both of these criteria are used in this research.Results of testing the first hypothesis; obtained that the growth of company (company growth) have a significant positive effect on profitability at PT. Mustika Ratu and Subsidiaries.Results of testing the second hypothesis; obtained that the growth rate of the company (company growth) has a negative effect is not significant on capital structure at PT. Mustika Ratu and Subsidiaries.Results of testing the third hypothesis; obtained that capital structure of company (capital structure) have a significant negative effect on profitability at PT. Mustika Ratu and Subsidiaries. Results of testing the fourth hypothesis; obtained that the hypothesis that firm size (firm size) have a significant positive effect on profitability not acceptable (not tested) in this study. The result of the fifth hypothesis testing; obtained that firm size (firm size) have a significant positive effect on capital structure at PT. Mustika Ratu and Subsidiaries. Then the variable of capital structure has not been tested as intervening variable in relationship between company growth with profitability and also company size with profitability.